Image Transmission Utilizing Amplitude Modulation in Rydberg Atomic Antenna - Peng Zhang; Shaoxin Yuan; Mingyong Jing; Jinpeng Yuan; Hao Zhang; Linjie Zhang (IEEE Photonics Journal)
Microwave electric field precision measurement based on Rydberg atomic quantum coherence effect has rapidly advanced in recent years, capitalizing on its high sensitivity, broad bandwidth, and traceability. The utilization of distinct Rydberg quantum states facilitates achieving an ultra-wideband measurement response across various microwave frequency bands, offering extensive applications in wireless communication, radar positioning, astronomical observation, and related domains. In this work, leveraging the Rydberg atomic antenna, we achieve simultaneous multi-frequency reception in the C-band (7.91 GHz, 5.106 GHz) and S-band (3.78 GHz) through amplitude-shift keying modulation. Furthermore, we encode RGB information from color image pixels onto 3 carrier frequencies in the C-band and S-band, while optimizing the multi-channel signal amplitude. The pixel information of the color image obtained by atomic demodulation realizes the high-fidelity digital color image transmission, with a root mean square error of 4.806, a mean square signal-to-noise ratio of 1.627, a peak signal-to-noise ratio of 29.998 and a structural similarity index of 0.9589. This study establishes an experimental groundwork for the utilization of Rydberg atomic antennas in ultra-wideband wireless communication and measurement.